Pneumolysin activates neutrophil extracellular trap formation. (2nd March 2016) - Nel, J. G.; Theron, A. J.; Durandt, C.; Tintinger, G. R.; Pool, R.; Mitchell, T. J.; Feldman, C.; Anderson, R.
Summary: The primary objective of the current study was to investigate the potential of the pneumococcal toxin, pneumolysin (Ply), to activate neutrophil extracellular trap (NET) formation in vitro . Isolated human blood neutrophils were exposed to recombinant Ply (5‐20 ng ml −1 ) for 30–90 min at 37°C and NET formation measured using the following procedures to detect extracellular DNA: (i) flow cytometry using Vybrant® DyeCycle™ Ruby; (ii) spectrofluorimetry using the fluorophore, Sytox ® Orange (5 μM); and (iii) NanoDrop ® technology. These procedures were complemented by fluorescence microscopy using 4′, 6‐diamino‐2‐phenylindole (DAPI) (nuclear stain) in combination with anti‐citrullinated histone monoclonal antibodies to visualize nets. Exposure of neutrophils to Ply resulted in relatively rapid (detected within 30–60 min), statistically significant ( P  < 0·05) dose‐ and time‐related increases in the release of cellular DNA impregnated with both citrullinated histone and myeloperoxidase. Microscopy revealed that NETosis appeared to be restricted to a subpopulation of neutrophils, the numbers of NET‐forming cells in the control and Ply‐treated systems (10 and 20 ng ml −1 ) were 4·3 (4·2), 14.3 (9·9) and 16·5 (7·5), respectively ( n  = 4, P  < 0·0001 for comparison of the control with both Ply‐treated systems). Ply‐induced NETosis occurred in the setting of retention of cell viability, and apparent lack of involvement of reactive oxygen species and Toll‐like receptor 4. In conclusion, Ply induces vital NETosis in human neutrophils, a process which may either contribute to host defence or worsen disease severity, depending on the intensity of the inflammatory response during pneumococcal infection.